THE CORRELATION BETWEEN: AWARENESS OF HISTORY, RELIGIOUS VALUES AND MULTIETHNIC UNDERSTANDING WITH TOLERANCE ATTITUDE - Nurasiah Nurasiah; Abdul Azis; Widia Munira (Paramita: Historical Studies Journal)
This research used descriptive method Correlation Ex Post Facto (CEPF). Participants in this research were 177 students from SMA Negeri department Banda Aceh. The author found the main problem of intolerance that is the low social behavior, attitudes individualistic, until the crisis of harmonization within individualistic students. Based on these problems, the authors designed a strategy in tackling the crisis of intolerance on students through the stages of correlation analysis Ex Post Facto (CEPF). The phases include test partial correlation analysis, simple regression and multiple regression. The results showed that: (1) there is a significant positive relationship between the sense of history with an attitude tolerance of students; (2) there is a significant positive relationship between religious values with tolerance of high school students  ; (3) there is a significant positive relationship between the understanding of multi-ethnic tolerance students; and (4) are jointly relationship between awareness of history, religious values and understanding of multi-ethnic tolerance with students. Based on the results of the study, authors state that the increased tolerance due to the high contribution of awareness of history, religious values and understanding of the multi-ethnic students through socialization in the process of teaching history.